The Development of Mass media in International Relations: In case of Al-Jazeera Effects in Middle East - Prakoso, Muhammad Pambudi (Parahyangan Center for International Studies, 2023)
The international network has a very important role in strengthening the solidarity and unity of the masses, in spreading information to the community by creating virtual communities. Al-Jazeera as one of the most reputable media outlets in the international arena and have considerable influence in society. They have a vital role in raising awareness to the people in case of religion, culture and issues in the world. In addition, more rapid and accessible information in the global media has been supported by information among countries that have changed the politics of the authorities. mass media in international relations that grow so fast recently by knowing that the media and politics are related each others with sharing the mutual benefit to each other. The author discusses Al- Jazeera achievements in changing and growing people's opinions on politics, the media as a vehicle for community empowerment, and more. By producing new concepts through information and news that raise awareness of the Middle East community, the region's unequal social and political conditions, and the Middle East's position. In the Middle East, things are changing, and people are becoming more aware of the value of freedom and democracy. Keywords : Development; Mass Media; Al-Jazeera; Effect